Proposal of a new specific test to assess the aerobic performance in judo - Figueiredo Foresti, Y.; dos Santos, D. R. A.; de Souza, R. A.; Higino, W. P. (Research Quarterly for Exercise and Sport, 2022)
Purpose: Judo is an intermittent sport, dependent on anaerobic metabolism as well as aerobic metabolism to generate energy during a match; however, there are few reliable tests to measure specific aerobic performance in judo. Thus, the present study aimed to propose a new specific and indirect method to assess the aerobic performance in judo athletes; it determined the inter-rater and test-retest reliability of this new protocol and correlated the new protocol with a valid laboratory test.